Basic psychological needs and subjective well-being in Portuguese older people - Couto, Nuno; Antunes, Raul; Monteiro, Diogo; Moutão, João; Marinho, Daniel A.; Cid, Luís (Anales de Psicología / Annals of Psychology, 2020)
This study’s goal is the validation of the Portuguese version of the Basic Need Satisfaction General Scale (BNSG-S: Sousa, Pais Ribeiro, Palmeira, Teixeira, & Silva, 2012) in a sample of Portuguese older people, and analyze through a structural equations model the effect of the Portuguese elderly individuals’ global perception about the satisfaction of basic psychological needs on subjective well-being. Two samples of Portuguese elderly people aged between 60 and 90 years old were considered in this study. The results reveal that only Model 3 of the BNSG-S (3 factors, 11 items) showed good results of adjustment to the data (χ²=103,16, df=41, SRMR=.05, TLI=.90, CFI=.93, RMSEA=.07, 90% CI=.05-.08). In the second part of the study, we verified that satisfaction of basic psychological needs has a positive effect on subjective well-being in Portuguese elderly people. In the presence of this evidence, we concluded that the Portuguese version of the BNSG-S can be used as a means to evaluate the satisfaction of the basic psychological needs of the older population and their satisfaction has a positive effect on subjective well-being in the Portuguese older population.